Preliminary study on the synthesis and high‒resolution NMR analysis of Naproxen and Ibuprofen esters. Issue 3 (2004) - Jankowski Jankowski, Christopher K. Christopher K.; LeClair LeClair, Gaetan Gaetan; Aumélas Aumélas, André André; Gonzalez-de la Parra Gonzalez-de la Parra, Mario Mario; Jimenez-Estrada Jimenez-Estrada, Manuel Manuel; Tejada Tejada, Veronica Veronica; Chilpa-Reyes Chilpa-Reyes, Ricardo Ricardo; Bélanger Bélanger, Jacqueline M. R. Jacqueline M. R.; Paré Paré, J. R. Jocelyn J. R. Jocelyn
Abstract : The synthesis and NMR analysis of several diastereoisomeric Naproxyl–Naproxenate, Naproxyl–Ibuprofenate and Ibuprofyl–Naproxenate esters are reported. The NMR high resolution spectra run in presence of the chiral shift reagents and variable temperature analysis were done to study the dynamic properties of these esters.